Stability Assessment of High and Steep Cutting Rock Slopes with the SSPC Method - Hongliang Tao; Guangli Xu; Jingwen Meng; Ronghe Ma; Jiaxing Dong (Advances in Civil Engineering)
The stability of high rock slopes has become a key engineering geological problem in the construction of important projects in mountainous areas. The original slope stability probability classification (SSPC) system, presented by Hack, has made obvious progress and been widely used in rock slope stability analysis. However, the selection and determination of some evaluation indexes in the original SSPC method are usually subjective, such as intact rock strength and weathering degree. In this study, the SSPC method based on geological data obtained in the prospecting tunnels was presented and applied. According to the field survey and exploration of the prospecting tunnels, the weathering degree of the slope rock mass was evaluated. The empirical equation for the maximum stable height of the slope was applied to the slope stability evaluation in the presented SSPC method. Then, the slope stability probability of numerous cutting slopes in the sandstone unit was evaluated using the presented system. Results of the Geostudio software based on the limited equilibrium analysis of the investigated slopes were compared with the results obtained by the SSPC method. The results indicate that the SSPC method is a useful tool for the stability prediction of high and steep rock slopes.